BARRIER PERCEPTION FACTORS AFFECTING THE ACCEPTANCE OF THE COVID-19 VACCINE IN SALATIGA CITY: Hubungan Faktor Penghambat Vaksinasi dengan Penerimaan Vaksin COVID-19 di Kota Salatiga - Lu'luil Ma'rifati; Ari Udijono; Nissa Kusariana (Jurnal Berkala Epidemiologi, 2023)
Background: In Salatiga City, COVID-19 immunization still needs to meet the 70% vaccination target needed to generate herd immunity. Vaccine skepticism and injection phobia can be barriers. A study of community barriers to COVID-19 vaccination and vaccine uptake is needed. Purpose: This study aimed to analyze barriers affecting the acceptance of the COVID-19 vaccine in Salatiga City. Methods: The study collected data from 323 Salatiga City people. Fear of pain, doubts about the COVID-19 vaccine, perception of fear of AEFI (Adverse Events Following Immunization), perception of accessibility of the COVID-19 vaccine, and the perception of information about the COVID-19 vaccine were independent variables in this study. Acceptance of COVID-19 vaccination is dependent. Data analysis using Chi-Square with 0.05 significance. Results: The results of this study found a relationship between fear of pain (p-value = 0.00), doubt about the COVID-19 vaccine (p-value = 0.00), perception of fear of AEFI (p-value = 0.00), perception of accessibility of COVID-19 vaccine (p-value = 0.00), and perception of information about COVID-19 vaccine (p-value = 0.00) and acceptance of the COVID-19 vaccine by Salatiga City residents. Conclusion: Perceived COVID-19 vaccination barriers affected vaccine acceptance. Acceptance of COVID-19 vaccination in Salatiga City is related to fear of pain, doubt about the COVID-19 vaccine, perception of fear of AEFI, perception of accessibility of the COVID-19 vaccine, and perception of information about the COVID-19 vaccine. Salatiga City's COVID-19 education efforts should focus on vaccine safety and side effects in collaboration with health cadres and cross-sector collaboration.